The Effectiveness of Edmodo as E-learning in English Learning Practice Discussion at Indonesia Senior High School - Putri Anjeli Kesuma; Andre Kasmara; Margaret Stevani (Journal on Education, 2023)
This research aimed to find out the effectiveness of the use of social networking media Edmodo on class discussions on practical learning of English; and the relationship between the use of social networking media Edmodo and students’ participation in class discussions on practical learning of English. The sample of this research was 32 students of class XI in the 2022/2023 academic year of Kebangsaan senior high school Medan, North Sumatra, Indonesia. This research was an experimental research type using a factorial design, where the test variable (x1) was the use of Edmodo social media, the control variable (x2) was without the use of Edmodo social media, the dependent variable (y1) consisted of students’ participation in class discussion in the first simulation on practical English teaching materials (y1), and the second simulation on practical English teaching materials (y2). The results of the MANOVA test proved that the effectiveness of using discussion forums using Edmodo to increase students' English learning participation. As a result, there were differences in students’ participation in class discussions in the first simulation on English practice teaching material (y1), and the second simulation on English practice teaching material (y2) with those who did not take part in discussions on the social networking media Edmodo (x2).